Muscle metabolism changes with age and maturation: How do they relate to youth sport performance? - Armstrong, N.; Barker, A. R.; McManus, A. M. (British Journal of Sports Medicine, 2015)
Aim: To provide an evidence-based review of muscle metabolism changes with sex-, age- and maturation with reference to the development of youth sport performance. Methods: A narrative review of data from both invasive and non-invasive studies, from 1970 to 2015, founded on personal databases supported with computer searches of PubMed and Google Scholar. Results: Youth sport performance is underpinned by sex-, age- and maturation-related changes in muscle metabolism. Investigations of muscle size, structure and metabolism; substrate utilisation; pulmonary oxygen uptake kinetics; muscle phosphocreatine kinetics; peak anaerobic and aerobic performance; and fatigue resistance; determined using a range of conventional and emerging techniques present a consistent picture. Age-related changes have been consistently documented but specific and independent maturation-related effects on muscle metabolism during exercise have proved elusive to establish. Children are better equipped for exercise supported primarily by oxidative metabolism than by anaerobic metabolism. Sexual dimorphism is apparent in several physiological variables underpinning youth sport performance. As young people mature there is a progressive but asynchronous transition into an adult metabolic profile. Conclusions: The application of recent developments in technology to the laboratory study of the exercising child and adolescent has both supplemented existing knowledge and provided novel insights into developmental exercise physiology. A sound foundation of laboratory-based knowledge has been established but the lack of rigorously designed child-specific and sport-specific testing environments has clouded the interpretation of the data in real life situations. The primary challenge remains the translation of laboratory research into the optimisation of youth sports participation and performance.